PENGARUH PROMOSI TERHADAP PENINGKATAN PENJUALAN PADA KOPERASI SERBA USAHA BALIEM ARABICA DI KABUPATEN JAYAWIJAYA - Togodly, Elisabet; Tarore, Henny Stientje; Tumbel, Tinneke Mesye (Sam Ratulangi University, 2018)
promotion is a persuasive, persuasive, urgent, persuasive, convincing communication. The hallmark of persuasive persuasive communication is that there are communicators who plan to organize the news / information and how they are delivered in order to have a certain effect on the attitudes and behavior of the recipient (target audience). Sales is the main purpose of the company's activities. Companies, in producing goods / services, have the ultimate goal of selling goods / services yersebut to the public. Therefore, sales plays an important role for companies to make products that products produced by the company can be sold and provide income for the company. Sales conducted by the company aim to sell the goods / services needed as a source of income to cover all costs in order to earn a profit. This study aims to determine the effect of promotion on sales increase in Baliem Arabica Business Cooperative in Jayawijaya Regency. The results of this study using a simple correlation and regression analysis showed that: the promotion has a very significant positive effect on the increase in sales. Thus the hypothesis that there is influence of promotion to increase sales acceptable. The companion of all Baliem Arabica business companions should pay attention to the promotion to increase cultivation so that the expected sales can be achieved.Keywords: Promotion, Sales Increase